Model and analysis of optimal color vision deficiency system - Ya'akup, Afiqamirul (2015)
The inability to recognize color has caused several problems to the patient daily life and in conducting certain color oriented activities. To help the patient cope with problem related to color, a color vision deficiency aided device is designed. This paper focuses on developing a user interface that can detect colors and show it as text on the screen of the device using the concept of augmented reality. The system basically consists of a mini computer, Raspberry PI and its own camera module as well as a LCD screen for display purposes. Raspberry PI is used due to its small and compact size and capability to carry out image processing. Programming using OpenCV library has been developed for optimal color detection, filtering and processing can be carried out easily. Various experiments have been carried out to test for the performance and functionality of the device. The result of the distance test for various benchmark shapes and colors show that the hue element is almost consistent whereas the saturation varies by roughly 49.3% and value by 30.5%. As for the range of detection, the minimum range is about 20 cm where the maximum range is up to 12 meter. The accuracy of the four base colors detection is about 68%.